Development Of Student-Based Work Sheet Open Ended Problem In Fraction Materials Class III Elementary School - Fatma, Rafiah (Berpusi Publishing, 2023)
The background of this research is that students do not think creatively in solving problems that exist in questions and teachers rarely give open questions to students. To develop students' thinking skills, the development of worksheets based on open ended problems is carried out. This study aims to develop Student Worksheets based on open ended problems in class III fraction material at SD Negeri 060849 Medan Barat with valid and practical criteria. This research is a type of research and development (Research and Development) with the ADDIE model. The location of this research was carried out at SD Negeri 060849 Medan Barat. The time of this research was carried out in March 2023 – April 2023. The population in this study were class III students at SD Negeri 060849 Medan Barat. The sample in this study amounted to 27 students. Data collection techniques in this study used a questionnaire. The results showed that the average result of the validation of material experts was 4,8, the average result of media experts was 4,9, and the average result of linguists was 4,9. Based on the results of the average validation from material experts, media experts, and linguists, an average of 4,8 is classified as a valid criterion. The percentage of teacher response questionnaires was 92% (very practical) and student response questionnaires were 85,2 % (very good). Thus, worksheets based on open ended problems in class III fraction material meet valid and practical criteria for use in learning.